Micro/Nanoengineered α‐Fe2O3 Nanoaggregate Conformably Enclosed by Ultrathin N‐Doped Carbon Shell for Ultrastable Lithium Storage and Insight into Phase Evolution Mechanism. Issue 4 (30th December 2019) - Xie, Dan; Li, Huan‐Huan; Shi, Yan‐Hong; Diao, Wan‐Yue; Jiang, Ru; Sun, Hai‐Zhu; Wu, Xing‐Long; Li, Wenliang; Fan, Chao‐Ying; Zhang, Jing‐Ping
Abstract: The Fe‐based transition metal oxides are promising anode candidates for lithium storage considering their high specific capacity, low cost, and environmental compatibility. However, the poor electron/ion conductivity and significant volume stress limit their cycle and rate performances. Furthermore, the phenomena of capacity rise and sudden decay for α‐Fe2 O3 have appeared in most reports. Here, a uniform micro/nano α‐Fe2 O3 nanoaggregate conformably enclosed in an ultrathin N‐doped carbon network (denoted as M/N‐α‐Fe2 O3 @NC) is designed. The M/N porous balls combine the merits of secondary nanoparticles to shorten the Li + transportation pathways as well as alleviating volume expansion, and primary microballs to stabilize the electrode/electrolyte interface. Furthermore, the ultrathin carbon shell favors fast electron transfer and protects the electrode from electrolyte corrosion. Therefore, the M/N‐α‐Fe2 O3 @NC electrode delivers an excellent reversible capacity of 901 mA h g −1 with capacity retention up to 94.0 % after 200 cycles at 0.2 A g −1 . Notably, the capacity rise does not happen during cycling. Moreover, the lithium storage mechanism is elucidated by ex situ XRD and HRTEM experiments. It is verified that the reversible phase transformation of α↔γ occurs during the first cycle, whereas only the α‐Fe2 O3 phase is reversibly transformed during subsequent cycles. This study offers a simple and scalable strategy for the practical application of high‐performance Fe2 O3 electrodes. Abstract : Lithium storage : A micro/nanoengineered α‐Fe2 O3 nanoaggregate conformably enclosed by an ultrathin N‐doped carbon shell achieves good cycling stability. Experiments give insight into the phase evolution mechanism during the electrochemical reaction processes.